Compression of the Femoral Vessels by a Pseudotumor after Metal-on-Metal Total Hip Arthroplasty - Yasuaki Tamaki; Tomohiro Goto; Takahiko Tsutsui; Tomoya Takasago; Keizo Wada; Koichi Sairyo (Case Reports in Orthopedics)
Here we present a case of pseudotumor following total hip arthroplasty (THA) that resulted in a circulatory disturbance caused by compression of the femoral vasculature. A 63-year-old man presented with pain, swelling, and redness of the left leg 5 years after primary metal-on-metal THA using the AML-Plus stem, Pinnacle® acetabular cup, and 36 mm diameter Ultamet™ metal head system (DePuy Orthopaedics, Warsaw, IN). Enhanced computed tomography and magnetic resonance imaging revealed a large cystic lesion extending from the left hip anteriorly to the intrapelvic region and compressing the left femoral vessels. Percutaneous puncture of the lesion yielded a dark red aspirate and the patient was diagnosed to have a pseudotumor causing compression of the femoral vessels. We performed revision surgery to replace the metal head and metal liner with a smaller ceramic head and polyethylene liner without removal of the stem. Corrosion of the head-neck junction was identified intraoperatively with no obvious wear on the bearing surfaces. The left leg swelling and redness improved immediately postoperatively. A large pseudotumor should be kept in mind as a cause of vascular compression with unilateral leg edema in a patient who has undergone metal-on-metal THA.